On the management of seismic activity - V.N. Strakhov; M. G. Savin (Геофизический журнал, 2013)
The problem of seismic hazard decrease with the help of artificial sources, mainly the powerful impulse MHD-generator is considered. It has been shown that powerful electric impulses during their action on source zones are able to provoke strong earthquakes before their natural term. A review of theoretical works dedicated to the problems of interpretation of controlled seismicity is given. The authors do not conceal the difficulties on the way of comprehending difficult seismic processes in such open, nonlinear dissipative system, which corresponds to real geo-medium as well as they denote a set of problems, which can be solved only due to performance of large-scale geophysical experiment with artificial sources (powerful impulse MHD-generators, seismic vibrators, electric generators et al.). A conclusion is made on the vital necessity of elaboration of Federal program of works to decrease seismic hazard, which integrates traditions of geophysical monitoring based on scientific foundation and the ideas of controlled seismic activity.